Under the Bridge: Trolling and the Challenges of Recruiting Software Developers for Empirical Research Studies - Kokinda, Ella; Moster, Makayla; Dominic, James; Rodeghero, Paige (IEEE/ACM International Conference on Software Engineering: New Ideas and Emerging Technologies Results (Online), 2023)
Much of software engineering research focuses on tools, algorithms, and optimization of software. Recently, we, as a community, have come to acknowledge that there is a gap in meta-research and addressing the human-factors in software engineering research. Through meta research, we aim to deepen our understanding of online participant recruitment and human-subjects software engineering research. In this paper we motivate the need to consider the unique challenges that human studies pose in software engineering research. We present several challenges faced by our research team in several distinct research studies, how they affected research, and motivate how, as researchers, we can address these challenges. We present results from a pilot study and categorize issues faced into three broad categories including participant recruitment, community engagement, and data poisoning. We further discuss how we can address these challenges and outline the benefits a full-study could provide to the software engineering research community.